A review of the genus Pycnoglypta Thomson, 1858 (Staphylinidae, Omaliinae, Omaliini) with notes on related taxa - Shavrin, Alexey V. (Zootaxa, 2016)
A review of Pycnoglypta Thomson, 1858, including a redefinition of the genus, is given. Lectotype of Omalium luridum Gyllenhal, 1813 is designated. The seven species of the genus are placed into three species groups, including the new monotypic baicalica group. Dropephylla sibirica (Mäklin 1878) comb. nov. is transferred from the genus Pycnoglypta and redescribed; consequently, the Dropephylla sibirica species group, which had been diagnosed before by Gusarov within the genus Pycnoglypta, is reestablished in place of the Dropephylla puella species group erected by Jászay & Hlaváč based on erroneous identification of the nominate species. A new synonymy is established: Dropephylla linearis (Zetterstedt 1828) = D. puella (J. Sahlberg 1880) syn. nov. (=Phyllodrepa puella J. Sahlberg 1880). A key to all species of Pycnoglypta and all Siberian and Far Eastern Dropephylla species is provided. Both male and female genitalia and terminalia as well as other main morphological structures are figured anew; distributional data are provided and mapped for all the species discussed.